Nature’s magic: how natural products work hand in hand with mitochondria to treat stroke - Cheng, Lin; Lv, Shangbin; Wei, Chengkai; Li, Sucheng; Liu, Hao; Chen, Yong; Luo, Zhaoliang; Cui, Hongyan (Frontiers in Pharmacology, 2025)
BackgroundMitochondria, as the energy factories of cells, are involved in a wide range of vital activities, including cell differentiation, signal transduction, the cell cycle, and apoptosis, while also regulating cell growth. However, current pharmacological treatments for stroke are challenged by issues such as drug resistance and side effects, necessitating the exploration of new therapeutic strategies.ObjectiveThis review aims to summarize the regulatory effects of natural compounds targeting mitochondria on neuronal mitochondrial function and metabolism, providing new perspectives for stroke treatment.Main findingsNumerous in vitro and in vivo studies have shown that natural products such as berberine, ginsenosides, and baicalein protect neuronal mitochondrial function and reduce stroke-induced damage through multiple mechanisms. These compounds reduce neuronal apoptosis by modulating the expression of mitochondrial-associated apoptotic proteins. They inhibit the activation of the mitochondrial permeability transition pore (mPTP), thereby decreasing ROS production and cytochrome C release, which helps preserve mitochondrial function. Additionally, they regulate ferroptosis, mitochondrial fission, and promote mitochondrial autophagy and trafficking, further enhancing neuronal protection.ConclusionAs multi-target chemical agents, natural products offer high efficacy with fewer side effects and present promising potential for innovative stroke therapies. Future research should further investigate the effectiveness and safety of these natural products in clinical applications, advancing their development as a new therapeutic strategy for stroke.